The protagonism of K-12 students through the development of smartphone applications - Medeiros, Giselle Araújo e Silva de (2021)
The importance of learning computational thinking in K-12 is well recognized today. Computational thinking encompasses problem solving as well as knowledge of algorithms and programming, which can be taught through the development of mobile applications. Using a visual block programming language such as App Inventor, middle school students can learn to develop functional applications for smartphones, allowing them to understand and apply concepts of computing, interface design among other skills. Adopting computational action as a pedagogical strategy allows to resolve problems in the local community, as part of computing education. In this context, the article presents a case study evaluating the learning experience of the students participating in the project "Young Programming Tutors", through the pedagogic practice "Make your first app", created by the initiative Computação na Escola/INCoD/INE/UFSC in 2018, which aims to teach computational thinking to middle school students through the development of applications. In addition, the students collaborate by teaching computing and knowledge and programming competencies to other students at their school. The results of this case study show that this pedagogical practice can contribute to the interest and motivation of the students, covering subjects with respect to their lives and community. Such perspectives tend to strengthen the construction of knowledge and the development of student skills, encouraging construction rather than just the consumption of technology